Challenges for supply chain management (logistics management) in petroleum industry - Zohari, Naser Hamad Obaid (2023)
The purpose of this study is to investigate the effect of pressure transients on the use of a water hydraulics machine in a food processor. Water is used as a pressure medium to control the movement of double-acting cylinders within a custom- built food-processing machine. The system employs Cartesian robotics movement, with one cylinder working horizontally and the other working vertically to provide compression. The machine is converted into a simple compression machine in this experiment so that the pressure transient during the process can be measured and analyzed. As a result, this paper presents an analysis of pressure transients during continuous compression tests of malleable, viscoelastic, elastic, and brittle materials. It is noted that several pressure transients are observed during the tests.